Effectivity of the Gold Sea Cucumber Supplementation (Stichopus hermanii) of Catalase Activity in Wistar Rat’s Submandibular with Oral Candidiasis - Ajeng Hanun Winny Khairina; Syamsulina Revianti; Nafi’ah (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: Oral candidiasis is common opportunistic infection in oral cavity caused by the fungal pathogen Candida albicans and it can develop to malignant such as a candida leukoplakia if it’s affected by cigarette smoke exposure. Purpose: To analysis the effectivity of Stichopus hermanii supplementation of catalase activity in Wistar rats submandibular with oral candidiasis. Materials and Methods: This study was post-test-only control group design, using 35 male Wistar rats were divided into 5 groups, Group1 is negative control, Group2 is positive control, Group3 is treatment control with Stichopus hermanii 0,0225 mg/g BB powder, Group4 is treatment control with Stichopus hermanii 0,045 mg/g BB powder) Group5 is treatment control with Stichopus hermanii 0,09 mg/kg BB powder). Oral candida infection was achieved by spray and cotton swab rolled over all parts of the mouth. After treatment, rats were euthanized and submandibular were biopsied to make histopathology slide for measure activity of enzim catalase with spectrophotometer λ 280 nm. Data were analyzed using One Way ANOVA and Tukey LSD test. Results: There are significantly differences catalase activity between K1&K2, K2&K3, K4&K1, K2&K4, K2&K5. Conclusion: Suplementation of Stichopus hermanii effectiv of catalase activity in wistar rat’s submandibular with Candida albicans A infection.